Exploring The Factors and Strategies Used to Cope with Speaking Anxiety of EFL Students During Online Learning - Vita Andini; Aridah Aridah; Iwan Setiawan (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
The research purpose is to know the factors about the students had several factors caused anxious in public speaking during online learning, which are lack of confidence, learner inhibition, lack of subject matter, excessive use mother tongue, lack of preparation, fear of making mistakes, and lack of vocabulary. In addition, the students have their strategies used to cope speaking anxiety which are preparation, relaxation, silent and improvisation. The conclusion of this study is most students had plans in place to reduce their nervousness before giving presentations or speaking in front of an audience. The research shows that several factors, including anxiety, are having an impact on students in second semesters